PENERAPAN TEKNOLOGI BUDIDAYA IKAN NILA (Oreochromis niloticus) MONOSEX JANTAN DI KOLAM BUNDAR UNTUK IBU-IBU DI DESA AWANG BANGKAL TIMUR - Rukmini Rukmini; Maya Amalia (Jurnal Abdi Insani, 2023)
The flood disaster that hit South Kalimantan in 2021 resulted in most fish cultivators not being able to raise fish in floating net cages again because they did not have much capital. Some fish cages that are still cultivating tilapia in floating net cages have very slow growth. The purpose of this PDWA activity is to increase knowledge and skills, meet the nutritional needs of families, and increase the income of members of the group of partner mothers in Awang Bangkal Timur Village, Banjar Regency, South Kalimantan. Activity Method (1) Extension and discussion. (2) Demonstration and participation. (3) Training and mentoring, and (4). Evaluation. The results of the PDWA activity were quite successful, namely from the demonstration plot of male monosex tilapia cultivation with artificial feeding for 3 months showed quite rapid growth. The average growth rate of tilapia is 240.3 grams kept for 3 months in a round pond, so this pilot can clearly prove to mothers, especially the target audience, that male monosex tilapia that is kept can be used as an effort to increase family income. . The final weight of the tilapia population was 237.975 kg with the amount of feed given for 3 months of 450 kg. Thus the feed conversion is 1.89. The evaluation value of the level of knowledge before explaining the theory averaged 8.47, after explaining the theory there was a significant increase in value, which was an average of 25.82. The results of data analysis showed that there was a change in the level of knowledge and skill level of the community regarding the technology of male monosex tilapia cultivation. The conclusions of the activity were (1) There was an increase in the knowledge of the partner group mothers regarding the technology that was presented. (2) There is an increase in the skills of partner group mothers after a demonstration or pilot is carried out.